Pengaruh Keikutsertaan Program P2MW dan Manajemen Keuangan terhadap Jiwa Kewirausahaan Mahasiswa di Universitas PGRI Wiranegara - Ika Yuni Aulia Restanti; Sugeng Pradikto (Jurnal Manajemen Riset Inovasi, 2025)
This study aims to analyze the influence of P2MW Program participation and financial management on the entrepreneurial spirit of Universitas PGRI Wiranegara students. The research employs a quantitative approach with a causal-comparative design. Data were collected through questionnaires distributed to 55 students who participated in the P2MW Program from 2022 to 2024, using a census technique. Analysis was conducted using SPSS software to examine the relationship between variables. This study highlights the importance of financial management and entrepreneurship programs in shaping students' entrepreneurial spirit.The findings are expected to contribute to the development of entrepreneurship training strategies in academic environments to produce competent and creative young entrepreneurs”